Analisis Supply Material Menggunakan Metode Economic Order Quantity Pada Proyek Mesin Pembersih Magazine Di Perusahaan Konstruksi FYZ - Annisa UL Mawadah; Andi Erna Mulyana (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2023)
The purpose of this work is to analyze the material stocks and the optimal amount of ordering costs for hollow and flat materials using the metrics studied in the billet washing machine project, which are the optimal order quantity, order frequency, total raw material, safety. . inventory, breakeven point and cost comparison. The method is economic order quantity (EOQ) data collection techniques using engineering, purchasing and financial interviews and analyzing company data collected by researchers, ie. cost and excel files recording actual material purchases for the magazine washing machine project. The results showed that the material supply process using EOQ can optimize the inventory costs of hollow and sheet materials, with the difference between ordering costs and inventory costs being IDR 105,627,563.02.